Comparison of Concepts of Islamic and Traditional Instructions in Indonesia - Mursid, Mursid; Muhibbin, Moh.; Suratman, Suratman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Inheritance law is closely related to the scope of human life, because all humans in particular will definitely experience death. There are various conceptions of inheritance used in Indonesia, including the conception of Islamic inheritance and the conception of customary inheritance. This study aims to compare the conception of Islamic and customary inheritance and their application in Indonesia. The type of research used is normative juridical with the Statute Approach and Conceptual Approach and the sources of legal materials used are primary, secondary, and tertiary laws. Next, collect legal materials for descriptive analysis. Based on the research that has been done, it is found that the comparison of the conception of Islamic and customary inheritance has similarities and differences in principle. The similarities between the conceptions of Islamic and customary inheritance, one of which explains the transfer of property, but the difference is that in Islamic inheritance the heir must die but in customary inheritance it is not required to die. The application of Islamic inheritance in Indonesia consists of a pluralism of teachings, for example the ahlus sunnah wal jamaa'h inheritance system (Shafi'i, Hanafi, Hambali and Maliki schools) and the most dominant is the Shafi'i school of thought. For the application of customary inheritance in Indonesia, it is influenced by the principle of lineage which is influenced by the form of ethnicity in the customary law environment.